Book review: Lakhwinder Singh and Anita Gill (Eds.). 2020. Agriculture Innovation Systems in Asia: Towards Inclusive Rural Development. (August 2020) - Mehta, Swati
Lakhwinder Singh and Anita Gill (Eds.). 2020. Agriculture Innovation Systems in Asia: Towards Inclusive Rural Development . London, UK and New York, NY: Routledge, Taylor & Francis Group, xxiv + 340 pp., ₹1, 495. ISBN: 978-0-367-14666-5 (Hardback).